Surface characteristics and molecular interactions of thin films between bubbles by molecular simulations - Tiefeng Peng; Tiefeng Peng; Yangyang Huai; Yangyang Huai (Frontiers in Chemistry)
IntroductionWhether in industrial production or daily life, froth plays an important role in many processes. Sometimes, froth exists as a necessity and is also regarded as the typical characteristic of products, e.g., froth on shampoo. Froth often makes an important contribution to product performance, such as in cleaning operations. On the other hand, froth may destroy the production process, such as in the textile and paper industry. Another example, ultra-stable froth accumulates on the thickener from flotation brings a series of difficulties to pumping, settling and dewatering operations, and would lead to pollution to the industrial circulating water treatment, thus it must be prevented.MethodsIn this work, the factors affecting the stability of froth, and relationship of bubble coalescence and film rupture was investigated, and molecular simulations (MD) were performed to study the aqueous molecular formation and surface characteristics of thin films between bubbles that contribute to the froth stability.ResultsThe detailed interfacial structure, molecular formation along Z-axis, angle distribution within the first and second layer, and also critical thickness were studied and discussed. The film rupture was validated and interpreted by the water-water interactions within the thin film, and these surface interactions were also examined using binding energy, dipole autocorrelation function (DAF). These simulations explicitly utilize polarizable potential model, incorporating many-body interactions, in which induced polarization plays a critical role in reproducing experimental observables and understanding physical behavior.DiscussionThe results provide beneficial insight for ultra-stable removal from microscopic view, and have direct benefits in dissolved air flotation used in mining industry, to develop efficient and sustainable processes for industries to minimize water and chemical usage.